Effects of mindfulness exercises as stand-alone intervention on symptoms of anxiety and depression: Systematic review and meta-analysis. (March 2018) - Blanck, Paul; Perleth, Sarah; Heidenreich, Thomas; Kröger, Paula; Ditzen, Beate; Bents, Hinrich; Mander, Johannes
Abstract: Mindfulness-based interventions (MBIs) are currently well established in psychotherapy with meta-analyses demonstrating their efficacy. In these multifaceted interventions, the concrete performance of mindfulness exercises is typically integrated in a larger therapeutic framework. Thus, it is unclear whether stand-alone mindfulness exercises (SAMs) without such a framework are beneficial, as well. Therefore, we conducted a systematic review and meta-analysis regarding the effects of SAMs on symptoms of anxiety and depression. Systematic searching of electronic databases resulted in 18 eligible studies (n = 1150) for meta-analyses. After exclusion of one outlier SAMs had small to medium effects on anxiety ( SMD = 0.39; CI : 0.22, 0.56; PI : 0.07, 0.70; p < .001, I 2 = 18.90%) and on depression ( SMD = 0.41; CI : 0.19, 0.64; PI : −0.05, 0.88; p < .001; I 2 = 33.43%), when compared with controls. Summary effect estimates decreased, but remained significant when corrected for potential publication bias. This is the first meta-analysis to show that the mere, regular performance of mindfulness exercises is beneficial, even without being integrated in larger therapeutic frameworks. Highlights: We investigated mindfulness exercises as a stand-alone intervention. Stand-alone mindfulness exercises exhibit positive effects on anxiety and depression. Future studies should investigate effects in clinical samples.